Indistinguishable encryption scheme under chosen plaintext attack (IND-CPA) - Huillca_Huallparimachi, Raul (2022)
Homomorphic encryption is a type of encryption with processing and evaluation capabilities on encrypted data. This paper examines the vulnerability with respect to the indistinguishable attack type under chosen plaintext attack (IND-CPA), existing with respect to security in homomorphic encryption. Homomorphic encryption performs different types of computations on encrypted data, some of them are partially homomorphic, fairly homomorphic, and fully homomorphic encryption. Partially homomorphic ciphers process only one type of operation, addition or multiplication; the fairly homomorphic ones that can process both operations, but for a limited set, and the fully homomorphic ones that allow processing and evaluation an arbitrary number of times. A chosen cleartext attack occurs in this type of encryption where the adversary knows the system, that is, the system has to be secure against an adversary who knows everything about it except the private key. The security levels present in the majority of completely homomorphic ciphers are sufficient for specific applications; the lack of the Indistinguishability property of a cryptosystem makes the production application of these types of encryption still impractical.